PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA JASA PENGIRIMAN BARANG YANG MENGALAMI KERUGIAN AKIBAT KONSUMEN TIDAK MEMBAYAR BIAYA PENGIRIMAN BARANG - Muhammad Rizki Ramadhan; Sri Maharani MTVN (Fakultas Ilmu Sosial dan Humaniora, 2025)
Legal Protection for Business Actors Which is legal protection obtained by business actors in carrying out their business activities. In carrying out their business activities, business actors have their rights and obligations that must be carried out properly. Business actors who experience losses due to consumers not paying the cost of freight forwarding services have rights that must be fulfilled. The problem raised in this thesis is that business actors are harmed by the actions of consumers who do not pay the delivery service fees that have been agreed by each party. For actions taken by consumers, business actors experience losses and do not get their rights and consumers have been considered to have committed acts of default in civil law. This research uses a normative juridical approach using a statutory approach and a conceptual approach. In this study, it was found that the position of business actors who suffered losses due to the actions of consumers who did not pay the cost of freight forwarding services had a more advantageous position because business actors had carried out their obligations by fulfilling existing achievements. Business actors have preventive legal protection and repressive legal protection and get the right to take legal remedies in accordance with the rules in the consumer protection law. Keywords : Legal Protection, Business Actors, Consumer Protection, Losses